SDSS J090152.05+624342.6: A NEW “OVERLAPPING-TROUGH” FeLoBAL QUASAR AT Z ~ 2 - Wang, Jing; Xu, Dawei; Wei, Jianyan (Frontiers in Astronomy and Space Sciences, 2017)
We here report an identification of SDSS\,J090152.04+624342.6 as a new ``overlapping-trough'' iron low-ionization broad absorption line quasar at redshift of $z\sim2.1$. No strong variation of the broad absorption lines can be revealed through the two spectra taken by the Sloan Digital Sky Survey with a time interval of $\sim6$yr. Further optical and infrared spectroscopic study on this object is suggested.